Activation of ADP-ribosylation factor regulates biogenesis of the ATP7A-containing trans-Golgi network compartment and its Cu-induced trafficking. - Holloway, Z; Grabski, R; Szul, T; Styers, M; Coventry, J; Monaco, A; Sztul, E (2007)
ATP7A (MNK) regulates copper homeostasis by translocating from a compartment localized within the trans-Golgi network to the plasma membrane (PM) in response to increased copper load. The mechanisms that regulate the biogenesis of the MNK compartment and the trafficking of MNK are unclear. Here we show that the architecture of the MNK compartment is linked to the structure of the Golgi ribbon. Depletion of p115 tethering factor, which causes fragmentation of the Golgi ribbon, also disrupts the MNK compartment. In p115-depleted cells, MNK localizes to punctate structures that pattern on Golgi ministacks dispersed throughout the cell. Despite altered localization MNK trafficking still occurs, and MNK relocates from and returns to the fragmented compartment in response to copper. We further show that the biogenesis of the MNK compartment requires activation of ADP-ribosylation factor (Arf)1 GTPase, shown previously to facilitate the biogenesis of the Golgi ribbon. Activation of cellular Arf1 is prevented by 1) expressing an inactive "empty" form of Arf (Arf1/N126I), 2) expressing an inactive form of GBF1 (GBF1/E794K), guanine nucleotide exchange factor for Arf1, or 3) treating cells with brefeldin A, an inhibitor of GBF1 that disrupts MNK into a diffuse pattern. Importantly, preventing Arf activation inhibits copper-responsive trafficking of MNK to the PM. Our findings support a model in which active Arf is essential for the generation of the MNK compartment and for copper-responsive trafficking of MNK from there to the PM. Our findings provide an exciting foundation for identifying Arf1 effectors that facilitate the biogenesis of the MNK compartment and MNK traffic.